Loss of definition of the submental contouring: correct diagnosis and treatment algorithm - Gladstone E. L. Faria; Clarissa L. Vilela; Alyne Queiroga Bastos; Carolina Freitas Tavares Silva; Ricardo F. Boggio (Sociedade Brasileira de Dermatologia (SBD), 2022)
The search for aesthetic procedures aimed at the loss of submental definition is increasing. A correct diagnosis is imperative for successful treatment and the reduction of complications. Localized adiposity, skin flaccidity, and loss of bone structure are the main findings. A treatment algorithm was discussed in this review, remembering, of course, the possibility of combined and sequential treatments for better results.